2016
DOI: 10.1002/etc.3525
|View full text |Cite|
|
Sign up to set email alerts
|

Population and life‐stage–specific effects of two herbicide formulations on the aquatic development of European common frogs (Rana temporaria)

Abstract: Environmental contamination is suggested to contribute to amphibian population declines. However, the effects of a contaminant on a particular amphibian species can differ among populations. The authors investigated the toxic effects of 2 herbicide formulations on different populations and on representative developmental stages of the European common frog (Rana temporaria). Larvae from forest populations were more sensitive to a commonly used glyphosate-based herbicide compared with individuals from agrarian l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…This is in line with the results from Adams and Brühl [16], where early larvae of R. temporaria (Gosner stage 20) were two times more sensitive than late larvae (Gosner stage 36) to the fungicide Folpan® 80 WDG with the same active ingredient folpet. Also Wagner et al [10] found late larval stages of R. temporaria to be less sensitive in acute tests with two herbicides. Interestingly, in our study early larvae of B. viridis at 26°C were least sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with the results from Adams and Brühl [16], where early larvae of R. temporaria (Gosner stage 20) were two times more sensitive than late larvae (Gosner stage 36) to the fungicide Folpan® 80 WDG with the same active ingredient folpet. Also Wagner et al [10] found late larval stages of R. temporaria to be less sensitive in acute tests with two herbicides. Interestingly, in our study early larvae of B. viridis at 26°C were least sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides were shown to have adverse effects on amphibians in several studies (e.g. [8][9][10][11][12], and are consequently identified as one of the main drivers in the global amphibian decline [13,14]. The actual toxicity of pesticides for amphibians depends on a number of factors, including the active ingredients [8],…”
Section: Leeb Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several studies found evidence for evolved pesticide tolerance in terms of decreased sensitivity in amphibian larvae of populations frequently exposed to pesticides, e.g. in Lithobates sylvaticus [19] or Rana temporaria [20]. The simplest behavioral response to minimize adverse effects might be to avoid a contamination.…”
Section: Introductionmentioning
confidence: 99%